The position of atomic particles in the foundational papers of Quantum Mechanics, 1925-1927 (Culturas Científicas, 2023)
We present an introductory study of the role of the particle concept in the foundational papers of quantum mechanics. We focus on the period, 1925-1927, which includes the analysis of the first papers by Heisenberg, Born, Jordan, Schrödinger and Dirac, and also the first formulation of Bohr's complementarity. Our aim is to discuss to what extent the concept of particle was questioned among the creators of the new theory, just at the time of its creation and when there was still no agreed or established interpretation. Subsequent developments, such as quantum field theory, put the validity of this concept under suspicion. We show that a historiographical analysis articulated by means of this concept makes it possible to characterize the relationship that the different authors of quantum mechanics maintained with the visualization of atomic processes. In some cases, such as that of Heisenberg, their evolution is particularly significant. Likewise, we will also quote some fragments where the authors considered claim for themselves the legacy of the old quantum theory, trying to legitimize their own developments on the basis of their coherence with the first discoveries of Planck, Einstein or De Broglie. From practically all of them we have found texts in this sense.
Keywords: electron; wave-particle duality; atomism; Heisenberg; Schrödinger